An analysis of surveillance screening for SDHB-related disease in childhood and adolescence. Issue 3 (March 2019) - Tufton, Nicola; Shapiro, Lucy; Sahdev, Anju; Kumar, Ajith V; Martin, Lee; Drake, William M; Akker, Scott A; Storr, Helen L
Abstract : Objective: Phaeochromocytomas (PCC) and paragangliomas (PGL) are rare in children. A large proportion of these are now understood to be due to underlying germline mutations. Here we focus on succinate dehydrogenase subunit B ( SDHB ) gene mutation carriers as these tumours carry a high risk of malignant transformation. There remains no current consensus with respect to optimal surveillance for asymptomatic carriers and those in whom the presenting tumour has been resected. Method: We undertook a retrospective analysis of longitudinal clinical data of all children and adolescents with SDHB mutations followed up in a single UK tertiary referral centre. This included index cases that pre-dated the introduction of surveillance screening and asymptomatic carriers identified through cascade genetic testing. We also conducted a literature review to inform a suggested surveillance protocol for children and adolescents harbouring SDHB mutations. Results: Clinical outcomes of a total of 38 children are presented: 8 index cases and 30 mutation-positive asymptomatic carriers with 175 patient years of follow-up data. Three of the eight index cases developed metachronous disease and two developed metastatic disease. Of the 30 asymptomatic carriers, 3 were found to have PGLs on surveillance screening. Conclusions: Surveillance screening was well tolerated in our paediatric cohort and asymptomatic paediatric subjects. Screening can identify tumours before they become secretory and/or symptomatic, thereby facilitating surgical resection and reducing the chance of distant spread. We propose a regular screening protocol commencing at age 5 years in this at-risk cohort of patients.